NASHA hyaluronic acid for the treatment of shoulder osteoarthritis: a prospective, single-arm clinical trial - McKee MD (Dove Medical Press, 2019)
Michael D McKee,1 Robert Litchfield,2 Jeremy A Hall,3 Tawana Wester,4 John Jones,4 Andrew J Harrison51Department of Orthopaedic Surgery, University of Arizona College of Medicine, Phoenix, AZ, USA; 2Department of Surgery, Fowler Kennedy Sport Medicine Clinical, London, ON, Canada; 3Department of Surgery, St Michael’s Hospital, Toronto, ON, Canada; 4Research and Development, Bioventus LLC, Durham, NC 27703, USA; 5Research and Development, Bioventus Cooperatief UA, Hoofddorp, NetherlandsBackground: Osteoarthritis of the shoulder or glenohumeral joint is a painful condition that can be debilitating. Intra-articular injection with hyaluronic acid should be considered for patients not responding adequately to physical therapy or anti-inflammatory medication.Methods: This was a single-arm, open-label, prospective study of a single intra-articular injection of NASHA (non-animal hyaluronic acid) in patients with symptomatic glenohumeral osteoarthritis. Patients were followed up for 26 weeks post-treatment, during which time rescue medication with acetaminophen was permissible. The study objective was to demonstrate that a single injection of NASHA is well tolerated with an over-6-month 25% reduction in shoulder pain on movement, assessed using a 100-mm visual analog scale.Results: Forty-one patients were enrolled, all of whom received study treatment. The mean decrease in shoulder pain on movement score over the 6-month study period was −20.1 mm (95% CI: −25.2, −15.0 mm), corresponding to a mean reduction of 29.5% (22.0, 37.0%). Statistically significant improvements were also observed in shoulder pain at night and patient global assessment. There was no clear change over time in the percentage of patients using rescue medication and mean weekly doses were below 3500 mg. Seventeen patients (41.5%) experienced adverse events, all of which were mild or moderate. Two adverse events (both shoulder pain) were deemed related to study treatment.Conclusion: This study provides preliminary evidence that a single injection of NASHA may be efficacious over 6 months and well tolerated in patients with symptomatic glenohumeral osteoarthritis. Larger studies are needed for confirmation.Keywords: Durolane®, glenohumeral joint, non-animal hyaluronic acid, osteoarthritis, shoulder, viscosupplementation